استهداف التطوير التنظيمي في المؤسسات الاقتصادية من خلال تفعيل تكنولوجيا المعلومات (Journal of Economics and Management Research, 2021)
جاءت هذه الورقة البحثية بهدف إبراز دور تكنولوجيا المعلومات في إحداث التطوير التنظيمي في مؤسستي "NCA Rouiba"و"Fruital Coca Cola". حيث تبين وجود علاقة ارتباط طردية غير قوية بين تكنولوجيا المعلومات والتطوير التنظيمي في هاتين المؤسستين، إذ بلغ معامل الارتباط 0.365 ** وهو ذو دلالة إحصائية عند مستوى معنوية 0.01. Abstract: This paper aims to highlight the role of information technology in creating organizational development in "NCA Rouiba" and "Fruital Coca Cola" corporations. Where it was found that there is a not strong direct correlation between information technology and organizational development in this two corporations, as the correlation coefficient was 0.365 **, which is statistically significant at the level of significance 0.01.